-1
x - 1
3(1−5x)x+1
1
3(1 - 5x)
Correct answer is D
5x+1−31−x−7x−1x2−1=?x+1
5(x−1)−3(−(x+1))−7x−1x2−1
= 5x−5+3x+3−7x−1x2−1
= x−1x2−1
= x−1(x−1)(x+1)
= 1x+1.
The numerator = 1.
Convert 2710 to another number in base three...
The smallest number such that when it is divided by 8 has a remainder of 6 and when it is divid...
Evaluate n2+1Cn+5 if n = 3 ...
If angle θ is 135°, evaluate cosθ ...
In ∆ PQR, P\hat{Q}P = 84^°, |Q\hat{P}R |= 43^° and |PQ| = 5cm. Find /QR/ in cm, correct to 1...
Find the length of a chord which subtends an angle of 90° at the centre of a circle whose radius...